Toward establishing precise 40Ar/39Ar chronologies for Late Pleistocene palaeoclimate archives: an example from the Lake Suigetsu (Japan) sedimentary record - Smith, V; Mark, D; Staff, R; Blockley, S; Ramsey, C; Bryant, C; Nakagawa, T; Han, K; Weh, A; Takemura, K; Danhara, T (Elsevier, 2011)
The varved Suigetsu (SG06) sediment core is potentially one of the most important and well-constrained mid-latitude palaeoclimate archives, recording continuous deposition during the last ∼150 kyrs. Numerous visible and non-visible volcanic ash layers form unique age markers within SG06. These ash layers are too fine and crystal-poor to be directly dated using the 40Ar/39Ar technique so the tephra were correlated to proximal volcanic deposits using their glass shard compositions. A high-precision 40Ar/39Ar sanidine age of 10.0 ± 0.3 ka (1σ, n = 34, MSWD = 0.71, p = 0.89) was obtained for the SG06-1288 (U-Oki) proximal tephra (Ulleungdo U4). 40Ar/39Ar yields a precision of ±3% near the younger limit of the method, with improved precision possible for older SG06 samples. Such 40Ar/39Ar ages for tephra layers can provide invaluable tie-points within the Lake Suigetsu SG06 sequence, giving independent verification of the core’s varve chronology, allowing for the calibration of cosmogenic nuclide production, and providing a precise chronology beyond the varve limit.